Mitochondria-Shaping Proteins and Chemotherapy - Xie, Longlong; Zhou, Tiansheng; Xie, Yujun; Bode, Ann M.; Cao, Ya (Frontiers in Oncology, 2021)
The emergence, in recent decades, of an entirely new area of “Mitochondrial dynamics”, which consists principally of fission and fusion, reflects the recognition that mitochondria play a significant role in human tumorigenesis and response to therapeutics. Proteins that determine mitochondrial dynamics are referred to as “shaping proteins”. Marked heterogeneity has been observed in the response of tumor cells to chemotherapy, which is associated with imbalances in mitochondrial dynamics and function leading to adaptive and acquired resistance to chemotherapeutic agents. Therefore, targeting mitochondria-shaping proteins may prove to be a promising approach to treat chemotherapy resistant cancers. In this review, we summarize the alterations of mitochondrial dynamics in chemotherapeutic processing and the antitumor mechanisms by which chemotherapy drugs synergize with mitochondria-shaping proteins. These might shed light on new biomarkers for better prediction of cancer chemosensitivity and contribute to the exploitation of potent therapeutic strategies for the clinical treatment of cancers.